2016
DOI: 10.18632/oncotarget.12612
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of crizotinib and pemetrexed-based chemotherapy in Chinese NSCLC patients with ROS1 rearrangement

Abstract: BackgroundROS1 rearrangement is a novel molecular subgroup of non-small-cell lung cancer (NSCLC). This study aimed to investigate the efficacy of crizotinib and pemetrexed-based chemotherapy in Chinese NSCLC patients with ROS1 rearrangement.ResultsA total of 2309 patients received ROS1 fusion detection and 51(2.2%) patients had ROS1 rearrangement. There was no significant difference between ROS1 fusion-positive and fusion-negative cohorts in demographic data. For the ROS1 fusion-positive patients, crizotinb-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 31 publications
2
32
1
1
Order By: Relevance
“…5 Similar anti-tumor activity was observed in several retrospective and single-arm studies. 811 Of note, the median PFS on crizotinib in these studies was shorter (range 9.1–13.4 months) than that observed in PROFILE 1001, but ORRs across studies were comparable. Based upon this activity, the U.S. Food and Drug Administration expanded crizotinib’s approval to include patients with advanced, ROS1 -positive NSCLC.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…5 Similar anti-tumor activity was observed in several retrospective and single-arm studies. 811 Of note, the median PFS on crizotinib in these studies was shorter (range 9.1–13.4 months) than that observed in PROFILE 1001, but ORRs across studies were comparable. Based upon this activity, the U.S. Food and Drug Administration expanded crizotinib’s approval to include patients with advanced, ROS1 -positive NSCLC.…”
Section: Introductionmentioning
confidence: 74%
“…Nonetheless, several recent studies have shown a comparable PFS to our series. 811 Interestingly, while ROS1 -positive patients had a longer median PFS on crizotinib compared to ALK -positive patients, there was no difference in OS between cohorts. While we cannot exclude the possibility that this was due to unaccounted for differences in patient characteristics, it is also possible that higher rates of next-generation targeted therapy use among ALK -positive patients may have offset the longer PFS on crizotinib among ROS1 -positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…ROS is a kinase receptor in the insulin receptor superfamily. Rearrangement occurs in 1–2% of non-squamous NSCLC ( 115 , 116 ). ROS-1 chromosomal rearrangement leads to STAT3, PI3K/AKT/mTOR, and RAS/RAF/MAPK activation, followed by cell growth, proliferation, and survival ( 117 ).…”
Section: Ros-1 Chromosomal Translocationmentioning
confidence: 99%
“…ROS-1 chromosomal rearrangement leads to STAT3, PI3K/AKT/mTOR, and RAS/RAF/MAPK activation, followed by cell growth, proliferation, and survival ( 117 ). ROS-1 translocation NSCLC patient is described to be young, female, non-smoker, and with advanced stage adenocarcinoma ( 115 , 117 120 ). The 5′ partners and the breakpoints of the ROS1 gene are variable ( 115 , 116 ), which may impact on the biology and benefit to therapy.…”
Section: Ros-1 Chromosomal Translocationmentioning
confidence: 99%
“…The EML4-ALK, CD74-ROS1 and KIF5C-RET constitute the major subset of those fusion variations. [12][13][14] ALK, ROS1 and RET rearrangement positive patients appears to be more common in young and never or light smokers diagnosed with adenocarcinoma. [15] Patients with ALK and ROS1 rearrangements can bene t from TKIs, such as crizotinib, which are now widely used in clinical practice.…”
Section: Introductionmentioning
confidence: 95%